Marginality and multidimensional poverty: A case study of Christian community of Lahore, Pakistan - Kanwal Zahra; Tasneem Zafar (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
Marginality and social exclusion are the pertinent concepts that researchers have tried to link directly or indirectly with the universal issues of poverty and resource constraints. This research tries to find out the extent of multidimensional poverty and its determinants among Christian community living in the slums of the Lahore city of Pakistan, after considering them at the margin of socio-economic systems due to some causal complexes that exclude them from the growth prospects. The urban context is the particular focus of this paper. On the basis of the analytical framework developed, study examines the relationship between marginality and poverty in a systematic manner and investigates the multidimensional poverty among the identified marginal group through a self-administered survey of 1380 individuals belonging to this minority group. We find these people as multidimensional poor, when we apply Alkire and Foster (2011) methodology. The study calculates intensity, depth and severity (M0, M1, and M2) measures of poverty to show more than half of population as multidimensional poor. The later analysis makes the use of Logit and Probit regression techniques to exhibit a strong impact of socio-economic and demographic determinants on the poverty profiles of Christian community.
Keywords: 330; marginality; multidimensional poverty (PDP); social exclusion